2009
DOI: 10.1021/jp907553b
|View full text |Cite
|
Sign up to set email alerts
|

Density Scaling and Dynamic Correlations in Viscous Liquids

Abstract: We use a recently proposed method [Berthier L.; Biroli G.; Bouchaud J.P.;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 55 publications
6
51
1
Order By: Relevance
“…It also shows that at fixed ‫ء‬ , the dynamic correlations are invariant to either T or , as expected from the density scaling of both the average dynamics and the dynamic correlations for the same value of ␥. Recent experiments 19 have shown that a similar result holds for the temperature derivatives of the two point dynamic correlation function T ͑t͒, which provides a lower bound to 4 ͑t͒. 16,17 This correspondence supports the validity of the experimentally accessible T ͑t͒ as an approximation to 4 ͑t͒.…”
Section: ͑4͒supporting
confidence: 70%
See 1 more Smart Citation
“…It also shows that at fixed ‫ء‬ , the dynamic correlations are invariant to either T or , as expected from the density scaling of both the average dynamics and the dynamic correlations for the same value of ␥. Recent experiments 19 have shown that a similar result holds for the temperature derivatives of the two point dynamic correlation function T ͑t͒, which provides a lower bound to 4 ͑t͒. 16,17 This correspondence supports the validity of the experimentally accessible T ͑t͒ as an approximation to 4 ͑t͒.…”
Section: ͑4͒supporting
confidence: 70%
“…16 Recent numerical and simulation works have shown that the dynamic correlation volume grows upon cooling. [17][18][19] However, very little is known about the combined temperature and density dependences of 4 ͑t͒. In particular, unexplored is the possibility of a description of the and T dependences of 4 ͑t͒ in terms of the scaling property established for the structural relaxation time [20][21][22] …”
Section: Density Scaling In Viscous Liquids: From Relaxation Times Tomentioning
confidence: 99%
“…lines of equal relaxation time). Contrary to previous reports [16,17] and to theoretical predictions [26,27], the extent of the spatial correlations in the dynamics is therefore not uniquely determined by the relaxation time. …”
Section: ∂F(t)contrasting
confidence: 94%
“…However, except for partial results at atmospheric pressure [11], this latter procedure was never attempted. Previous pressure studies along several isobars considered the crudest bound on χ 4 (t) only [16,17].…”
Section: ∂F(t)mentioning
confidence: 99%
“…A recently developed four-point correlation method 14 allows to estimate the size of this region from the temperature dependence of, say, the dielectric susceptibility [47][48][49] . The average number of inherent states in such a cooperatively rearranging region can be calculated from the asymmetry model 23 , because the f N for just two inherent states with asymmetry 4k B T in the core is 0.012.…”
Section: Discussionmentioning
confidence: 99%